Komunikasi Virtual Melalui Media Instagram Pada Remaja - Mega Sihombing; Noyanta Luga; Rachel Mia L. Lumbantoruan; Hindi Agus Mardin Laia; Epifania Buulolo (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Virtual communication is communication that uses media and internet networks, where this communication does not require meeting directly or face to face with the person you are talking to. Teenagers use a lot of virtual communication to communicate with their friends via social media such as Instagram. The aim of this research is to find out how virtual communication is carried out by teenagers and to find out the use of each feature on Instagram as a communication tool. This research uses New Media theory as a basis for writing this thesis. The informants in this study were 5 people. The results of this research are that virtual communication carried out by teenagers plays a very important role in communicating in the current era, because there are still many teenagers who use virtual communication when communicating. Virtual communication on Instagram media has many features for communicating which means teenagers can choose to communicate virtually via any feature. The research method uses qualitative with data collection using interviews and documentation.